Majelis Ta’lim Online Sebagai Wadah Pendidikan dan Penguatan Karakter Mahasiswi Politeknik Elektronika Negeri Surabaya - Firdiyanti Al Ma'idha; Elin Farichatul Jannah; Imamul Arifin (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2021)
This research has the aim of describing the Taklim Online Council as a forum for education and character strengthening for students of the Surabaya State Electronics Polytechnic. Sources of information in this research are observations, informants (interviews), documentation, and literature studies. The author raises this theme because there are so many behavior changes, especially in students related to morals, and character. Even though students are a measure of the nation's future success. This research is based on theories from various experts and some take theories from internet sites. The results of the study show (1) the implementation of the Taklim Online Council as a forum for education and character strengthening for Surabaya State Electronics Polytechnic students, and (2) the role of the Online Taklim Council as a forum for education and character strengthening for the Surabaya State Electronics Polytechnic students. In this study, it can be seen that Majelis Taklim Online is a form of Character Building, namely as a solution in an effort to create and enforce one's morals and character, this is in accordance with the mission of the Prophet Muhammad SAW to strive for a good character.